A colorimetric chemical tongue detects and distinguishes between multiple analytes. Issue 23 (21st October 2022) - Lim, Francis Buan Hong; Lei, Tingjun; Fernandez, Gabriella; Lopez, Nicole; Chu, Andre-Lorenz; Valiente, Allan; Nagesetti, Abhignyan; Nelson, Andy; Schmidt, Kerstin; Chang, Ta Chen; Piloto, Obdulio; Cheong, Ian
Abstract : The very photoinitiators used to polymerize hydrogels can react with analytes to produce distinctive colorimetric profiles. Abstract : The rate-limiting step for diagnostics development is the discovery and validation of biomarker analytes. We describe a new analyte-agnostic and label-free approach based on colorimetric reactions involving type I polymerization photoinitiators. We demonstrate that a chemically diverse array of hydrogels embedded with cleaved type I photoinitiators could act as microreactors, undergoing colorimetric reactions with bound analytes. The colorimetric signatures produced were visually distinctive and readable with a flatbed document scanner. Signatures of a broad range of sample types were accurately differentiated by unsupervised clustering without knowledge of any analytes bound to the array. The principles described have the potential to enable scalable and cost-effective analysis of complex samples.